GS SOIL (assessment and strategic development of inspire compliant geodata-services for european soil data) - Figueiredo, Carlos; Gonçalves, Maria De Conceição; Revez, Gonçalo; Martins, Rui; Tilsner, Dirk (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
This paper presents the GS SOIL project, which is currently running under the eContemPlus European program. The overall project objectives are described, focusing on the contribution and adoption of the INSPIRE directive, in the soil thematic area (Annex III), by the EU countries. This document also presents the results and outcomes of the project after the first 9 months of execution, with special focus on the conceptual architecture of the GS SOIL infrastructure, composed by a Portal and a set of open tools and services made available to the soil community, intended to allow the sharing of soil data among the EU member states. (en)
Keywords: INSPIRE – Annex III theme SOIL; metadata; portal; ferramentas open-source; GeoFOSS